Systematic Customer Value Analysis: A Case Study in the Automotive Industry - Çakmak, Tolga; Altun, Koray (Society of Sytematic Innovation, 2021)
Providing high quality with competitive prices is generally essential in the automotive industry because of the customers (directly automotive OEMs and indirectly their end-users) demanding new and costly features without showing additional willingness to pay. For this reason, accurate analysis of customer value can be very helpful for developing new concepts, and hence for correct positioning in this competitive area. Although one of the most important parts of the engine in an automobile is the clutch, there are very limited studies on its value analysis in the literature. Correspondingly, to fill this gap, this paper analyses the customer value of automotive clutch components and their functions by using a two-phase QFD methodology, and a fuzzy-logic based data-fusion methodology. While the former phase determines relative weights of the bene-fit through the House of Quality, the latter phase performs the parts (and cost) deployment to determine the costs of the clutch functions by using a reverse costing analysis incorporating the product teardown cost in-formation. Having obtained benefit, cost, and technical difficulty information, a fuzzy-logic model evaluates the competitive importance of each clutch function. This work identifies the three most important clutch functions and their related subcomponents.
Keywords: Automotive clutch; customer value analysis; fuzzy systems; quality function deployment